AVALIAÇÃO DA VARÍOLA EM CULTIVARES DE MAMOEIRO NA REGIÃO DO ECÓTONO CERRADO-PANTANAL - PERES, Nathália Dias; AMORIM, Andressa Cristina dos Santos; ANDRADE, Isadora Luciano; SILVA, Leonardo Gomes Duran; CELOTO, Mercia Ikarugi Bomfim; SILVA, Adriana de Castro Correia (ANAIS DO ENIC, 2020)
-